Distinguishing clinical and genetic risk factors for suicidal ideation and behavior in a diverse hospital population - Sarah M. C. Colbert; Lauren Lepow; Brian Fennessy; Nakao Iwata; Masashi Ikeda; Takeo Saito; Chikashi Terao; Michael Preuss; Jyotishman Pathak; J. John Mann; Hilary Coon; Niamh Mullins (Translational Psychiatry)
Abstract Suicidal ideation (SI) and behavior (SB) are major public health concerns, but risk factors for their development and progression are poorly understood. We used ICD codes and a natural language processing algorithm to identify individuals in a hospital biobank with SI-only, SB, and controls without either. We compared the profiles of SB and SI-only patients to controls, and each other, using phenome-wide association studies (PheWAS) and polygenic risk scores (PRS). PheWAS identified many risk factors for SB and SI-only, plus specific psychiatric disorders which may be involved in progression from SI-only to SB. PRS for suicide attempt were only associated with SB, and even after accounting for psychiatric disorder PRS. SI PRS were only associated with SI-only, although not after accounting for psychiatric disorder PRS. These findings advance understanding of distinct genetic and clinical risk factors for SB and SI-only, which will aid in early detection and intervention efforts.